Моделирование процесса усталостного разрушения зубцов крайних пакетов сердечника статора мощных турбогенераторов - Васьковский, Юрий Николаевич; Шумилов, Юрий Андреевич; Шторгин, Александр Валерьевич (НТУ "ХПИ", 2009)
Предложена расчетная модель, объясняющая возможные причины разрушения зубцов крайних пакетов сердечника статора мощных турбогенераторов резонансными явлениями в зубцах.

The computing model of the tooth's fatigue destruction process in the end packets of powerful turbogenerator stator core are proposed and explained it by resonant phenomena in the tooth's under influence of the core vibrations.
Simulation of the tooths fatigue destruction process in the end packets of powerful turbogenerators stator core
Keywords: резонансное явление; вибрация сердечника статора; вихревые токи; расслоение зубца; powerful turbogenerator; stator core; teeth destruction; resonance